Mild pericyte deficiency is associated with aberrant brain microvascular flow in aged PDGFRβ+/− mice. Issue 12 (December 2020) - Watson, Ashley N; Berthiaume, Andree-Anne; Faino, Anna V; McDowell, Konnor P; Bhat, Narayan R; Hartmann, David A; Shih, Andy Y
The receptor tyrosine kinase PDGFRβ is essential for pericyte migration to the endothelium. In mice lacking one allele of PDGFRβ (PDGFRβ +/− ), previous reports have described an age-dependent loss of pericytes in the brain, leading to cerebrovascular dysfunction and subsequent neurodegeneration reminiscent of that seen in Alzheimer's disease and vascular dementia. We examined 12–20-month-old PDGFRβ +/− mice to better understand how pericyte loss affects brain microvascular structure and perfusion in vivo. We observed a mild reduction of cortical pericyte number in PDGFRβ +/− mice (27% fewer cell bodies) compared to controls, but no decrease in pericyte coverage of the endothelium. This mild degree of pericyte loss caused no discernable change in cortical microvascular density, length, basal diameter or reactivity to hypercapnia. Yet, it was associated with an increase in basal blood cell velocity, primarily in pre-capillary arterioles. Taken together, our results suggest that mild pericyte loss can lead to aberrant cerebral blood flow despite a lack of apparent effect on microvascular structure and reactivity.